RIFM fragrance ingredient safety assessment, hexyl isovalerate, CAS Registry Number 10032-13-0. (15th July 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: Summary: The existing information supports the use of this material as described in this safety assessment. Hexyl isovalerate was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from read-across analog hexyl isobutyrate (CAS # 2349-07-7) show that hexyl isovalerate is not expected to be genotoxic. Data on read-across analog propyl (2S)-2-(1, 1-dimethylpropoxy)-propanoate (CAS # 319002-92-1) provide a calculated MOE >100 for the repeated dose toxicity and reproductive toxicity endpoints. Data from read-across analog hexyl 2-methylbutyrate (CAS # 10032-15-2) do not indicate that hexyl isovalerate is a skin sensitizer. The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; hexyl isovalerate is not expected to be phototoxic/photoallergenic. The local respiratory toxicity endpoint was evaluated using the TTC for a Cramer Class I material, and the exposure to hexyl isovalerate is below the TTC (1.4 mg/day). The environmental endpoints were evaluated; hexyl isovalerate was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: Hexyl isovalerate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.